ANALISIS EFEKTIVITAS CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM MENYELESAIKAN MASALAH SOSIAL LINGKUNGAN PERUSAHAAN - Supriadinata, Wahyu; Goestaman, Imanuel (University of Surabaya, 2013)
This research study aims to find out about how a CSR program is implemented and what kind of benefits earned by the company, and how feedback from the local society as an long term investment for the company. This research study used a qualitative approach using the descriptive research method. This research study aims to determine how the CSR program was implemented and what the long-term impact on the implemented CSR by the company. The study was conducted at the TBBM Depot Ende which is a marketing unit V PT. Pertamina (Persero) and the research begin on January 23, 2013 until February 17, 2013. From this study it can be concluded that CSR programs are planned before, almost whole implemented. However, in practice there are still weaknesses appear, makes the result of the implementation of the program is not maximized. these weaknesses can be fixed by giving recomendation which is a measurement and clear reporting needed, so that the information obtained can be used as an evaluation of the implementation of the next program.